2014
DOI: 10.1007/s11096-014-9927-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacist’s role in implementing a smoking cessation intervention in a Swiss regional hospital: an exploratory study

Abstract: A moderate-intensity smoking cessation intervention in hospitalized patients was associated with a higher quit rate than in control groups from other studies, and their readiness to quit generally improved at least 1 month after hospital discharge. A clinical pharmacist trained for smoking cessation counselling can play a key role in providing such interventions, including the assessment of pharmacotherapy interactions with tobacco smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“… 26 Awareness about existing tobacco policies might influence the effectiveness of this group of health professionals as advocates for the support of smoke-free policies in Nigeria. 21 Relevant programs to increase awareness about existing tobacco control laws will be beneficial to pharmacists. Their current lack of knowledge about existing tobacco control laws within their environment may need to be addressed in designing these programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Awareness about existing tobacco policies might influence the effectiveness of this group of health professionals as advocates for the support of smoke-free policies in Nigeria. 21 Relevant programs to increase awareness about existing tobacco control laws will be beneficial to pharmacists. Their current lack of knowledge about existing tobacco control laws within their environment may need to be addressed in designing these programs.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies on pharmacists in tobacco control research have focused on their role in providing tobacco cessation services largely ignoring their possible roles in promoting policy. 20 , 21 Pharmacists’ knowledge of tobacco and their attitudes towards smoke-free policies may influence their role as advocates for smoke-free policies within their communities. However, literature is sparse on the knowledge of health-related effects of tobacco and the attitudes towards smoke-free policies among pharmacists in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that moderate-intensity smoking cessation intervention from a pharmacist in the hospital led to a higher quit rate than those reported in control groups of other studies. Additionally, readiness to quit improved one month after discharge supporting the role of the pharmacist in tobacco cessation interventions [6]. Lastly, an ongoing study by Thomas et al is focusing on a pharmacist-led intervention program in the hospital environment.…”
Section: Impact Of a Pilot Pharmacy-led Tobacco Cessation Medicationmentioning
confidence: 92%
“…103 Prescription smoking cessation medications include bupropion and varenicline. 104 A recent Canadian survey shows that pharmacist-led intervention resulted in more than 70% of patients using nicotine replacement therapy for smoking cessation. 105…”
Section: Cvd Preventionmentioning
confidence: 99%